Generation Z: Fitting Project Management Soft Skills Competencies—A Mixed-Method Approach - Magano, José (2021)
Generation Z is arriving in the workforce. Do these youngsters have the skills and traits to fit project teams? This study reviews the literature concerning project management competencies and the traits that are associated with Generation Z. To deepen the understanding of its members (Gen Zers) traits, we explore the self-awareness of their profile, strengths and weaknesses with an empirical study. We used a mixed-method approach, implementing a survey on a sample of 211 college students about to enter the labor market. Comparing our survey results with the literature, we identified differences that reveal some of the lack of awareness of Gen Zers about their traits. Further analysis also revealed a significant correlation between the most highlighted Generation Z traits and essential project management soft skills, pointing to Generation Z as a promissory asset in the project management field. However, other essential project management (PM) soft skills were not grounded in personality traits. Our findings, namely the lack of awareness and association results, suggest the need for further research on educational approaches and re-thinking and targeting education and training policies that could strengthen Generation Z soft skills. Our results also suggest reflections about whether the Gen Zers traits fit the PM competencies sought by organizations.